A comprehensive proteomic analysis of elaioplasts from citrus fruits reveals insights into elaioplast biogenesis and function. Issue 1 (7th February 2018) - Zhu, Man; Lin, Jiajia; Ye, Junli; Wang, Rui; Yang, Chao; Gong, Jinli; Liu, Yun; Deng, Chongling; Liu, Ping; Chen, Chuanwu; Cheng, Yunjiang; Deng, Xiuxin; et al.
Abstract: Elaioplasts of citrus peel are colorless plastids which accumulate significant amounts of terpenes. However, other functions of elaioplasts have not been fully characterized to date. Here, a LC–MS/MS shotgun technology was applied to identify the proteins from elaioplasts that were highly purified from young fruit peel of kumquat. A total of 655 putative plastid proteins were identified from elaioplasts according to sequence homology in silico and manual curation. Based on functional classification via Mapman, 50% of the identified proteins fall into six categories, including protein metabolism, transport, and lipid metabolism. Of note, elaioplasts contained ATP synthase and ADP, ATP carrier proteins at high abundance, indicating important roles for ATP generation and transport in elaioplast biogenesis. Additionally, a comparison of proteins between citrus chromoplast and elaioplast proteomes suggest a high level of functional conservation. However, some distinctive protein profiles were also observed in both types of plastids notably for isoprene biosynthesis in elaioplasts, and carotenoid metabolism in chromoplasts. In conclusion, this comprehensive proteomic study provides new insights into the major metabolic pathways and unique characteristics of elaioplasts and chromoplasts in citrus fruit. Citrus fruits: The proteins of elaioplasts: A study of the proteins in bodies called elaioplasts in citrus fruit cells will help to clarify elaioplast formation and functions. Plant cells contain several types of membrane-bound bodies called plastids, with elaioplasts being an incompletely characterized type. They are known to store oils in the cells, especially molecules called terpenes that influence the fragrances and flavors of citrus fruits. Researchers in China, led by Yunliu Zeng at Huazhong Agricultural University, analyzed the protein molecules in elaioplasts of kumquat peel to investigate possible roles for elaioplasts other than oil storage. They identified more than 600 proteins and assigned likely functions to many. The results suggest the proteins are involved in chemical energy transactions and the manufacture of various categories of biomolecules. This will guide research to fully characterize the activities and significance of elaioplasts.